The Influence of Foaming Agent and Cake Thickness on the Drying Process Tomatoes Using a Tray Dryer - Tri Hariyadi; Herry Santoso; Judy Retti Witono (Reaktor, 2018)
Moisture content of tomato (Licopersicon esculentum Mill.) is very high, so easily damaged due to physical impact, enzyme and microbes activity. Further processing is necessary in order to improve shelf life, one way is drying method. This work studied the effect of foaming agent and cake thickness in tomato drying using tray dryer at various temperatures. Foaming agent is used to convert the material into foam, so that the drying temperature can be set relatively low to preserves color, aroma and nutrient composition of the material. The tray dryer is used, because it is simple and the operation cost is relatively cheap. In this work, tomatoes were sliced, crushed for 10 minutes using blender, separated from the seeds and residues with a 60 mesh sieve, and then mixed with dextrin and foaming agent Tween 80 each by 5% weight respectively. Each mixture was blended for 10 minutes. The tray dryer was filled with hot air at 2.0 m/sec with temperature variation of 40, 50, 60 and 70ºC and cake thickness variation of 2 and 4 mm. The results obtained, drying at 50° C is faster than 40º C, while 50 to 70º C is relatively the same. The thicker the cake, the slower the drying time. Performance of foaming agent Tween 80 compared to chemical foaming agent is a natural egg white powder. Drying with a foaming agent Tween 80 faster than egg white powder. Keywords: cake thickness; foaming agent; tomato; tray dryer